Uma avaliaç\~ao de impacto de política de segurança pública: O programa estado presente do espírito santo - Daniel Cerqueira; Darcy Ramos da Silva Neto; Danilo Santa Cruz Coelho; Gabriel de Oliveira Accioly Lins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– There was a decrease of 10.2% in the number of homicides in the State of Espírito Santo, between 2010 and 2014. During this period, substantial investments were allocated in a policy focused to reduce homicide, based on the organization of prison system and on the "Estado Presente em Defesa da Vida" program. The purpose of this paper is to investigate whether the public policy pursued in the state affected its violent lethality rate. This work used the synthetic control methodology proposed by Abadie, Diamond and Hainmueller (2010). The results indicate that the number of homicides would have increased by 29% in the period if the policy had not been adopted. Comparing the financial costs corresponding to the implementation of the policy, with the statistical value of lives saved, estimated by Cerqueira (2014), we conclude that each real invested generated a social welfare gain equivalent to R 2.4.
Keywords: O10; K42; C40; 330; synthetic control; homicide rate; public security policy; Brazil